Tingkat Pengetahuan Petani Kelapa Sawit Dalam Penerapan Good Agricultural Practices (GAP): Sebuah Analisis Rating Scale - Nayo Ayu Saqori Nasution; Ismiasih Ismiasih; Siwi Istiana Dinarti (JSEP (Journal of Social and Agricultural Economics), 2023)
Palm oil is a strategic commodity in the plantation sector in Indonesia. The government's recommendation in agricultural development, especially oil palm commodities, is to apply the principles of Good Agricultural Practices (GAP) in its cultivation. This study aims to determine the level of knowledge of farmers in the application of GAP in oil palm cultivation activities. The research sample was determined purposively with a total of 30 farmers. Data was collected by means of observation, questionnaires, and interviews. Data analysis was carried out using a qualitative descriptive method. The results showed that the level of farmers' knowledge of the application of GAP in oil palm cultivation was in the moderate category with a score of 1.83. Meanwhile, farmers in oil palm cultivation activities starting from land clearing, nursery, planting, maintenance, harvesting to marketing have not fully implemented the GAP principles. This is because there is no access for farmers to receive information about the GAP principle in oil palm cultivation